Aplikasi Drone Militer Dengan Produk Alutsista Indonesia untuk Over the Horizon Operations - Denny Lesmana; Yudha Permana; Budi Santoso; Ardian Infantono (Prosiding Seminar Nasional Sains Teknologi dan Inovasi Indonesia (SENASTINDO), 2021)
Drones/unmanned aircraft are one of the technologies in the defense sector that are included in the Indonesian government's strategic program. In the era of Information technology and society 5.0, the use of high technology is indispensable in overcoming various problems, especially Indonesia which has a large area. Drones can be a multifunctional platform that can play a role in War Military Operations (OMP) and Military Operations Other Than War (OMSP). The use of drones in the military is generally used as part of "Over The Horizon Operations", where all devices related to operations such as combat vehicles, weapons, and personnel communication tools become one unit in the "Battle Management System". The use of drone technology will be able to reduce the risk of pilots as well as the cost efficiency of their operations. With the flexibility of the role shown by the presence of drones, it can be a solution to various problems related to the needs of the users themselves, such as illegal fishing, illegal immigrants, piracy, floods, forest fires, terrorism, and military infiltration of other countries.